2020
DOI: 10.3390/rs12071160
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Estimating Tropical Forest Canopy Height from Planet Dove Imagery

Abstract: Monitoring tropical forests using spaceborne and airborne remote sensing capabilities is important for informing environmental policies and conservation actions. Developing large-scale machine learning estimation models of forest structure is instrumental in bridging the gap between retrospective analysis and near-real-time monitoring. However, most approaches use moderate spatial resolution satellite data with limited capabilities of frequent updating. Here, we take advantage of the high spatial and temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…In our study, the uncertainty analysis for AGB and CH estimation was carried out following the procedure adopted by Csillik et al [68,69]. We grouped the estimated values of AGB and CH (separately) into 10 bins using the natural breaks method and computed the RMSE in percentage (%) for each bin.…”
Section: Accuracy Assessment and Uncertainty Analysismentioning
confidence: 99%
“…In our study, the uncertainty analysis for AGB and CH estimation was carried out following the procedure adopted by Csillik et al [68,69]. We grouped the estimated values of AGB and CH (separately) into 10 bins using the natural breaks method and computed the RMSE in percentage (%) for each bin.…”
Section: Accuracy Assessment and Uncertainty Analysismentioning
confidence: 99%
“…The remaining 22–25% of unexplained variance can be minimized by using additional remotely sensed predictors and image processing techniques. For example, texture analysis on high resolution Planet data [ 18 , 54 ], hyperspectral data [ 55 ], or other multispectral imagery [ 56 58 ] have been successfully used for aboveground biomass and carbon estimation purposes. However, using extra predictors will require a trade-off between accuracy of the model, computational resources needed and the temporal frequency of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although representing a major advancement in estimating 3D forest structure, these current spaceborne laser observations are restricted to very narrow footprints, which are insufficient to map wall-towall canopy heights over larger areas. Recent studies have shown that the laser-derived canopy heights can be extrapolated through different combinations with other satellite observations and machine learning techniques (Csillik et al, 2020;Fagua et al, 2019). Typically, the canopy heights from laser measurements are extrapolated using textural information from active microwave sensors (e.g.…”
Section: Forest Parameters From Satellitesmentioning
confidence: 99%